2009
DOI: 10.1242/jeb.030866
|View full text |Cite
|
Sign up to set email alerts
|

Changes in thyroid hormone reception precede SWS1 opsin downregulation in trout retina

Abstract: SUMMARYRainbow trout undergo natural cone degeneration and thus are interesting models for examining mechanisms of neural degeneration. They have ultraviolet-sensitive (UVS) cones that are lost over most of the retina during development; only a small functional population remains in the dorsal retina. How this spatial distribution of UVS cones is maintained is unclear. Thyroxine (T4) induces UVS cone loss, and local thyroid hormone regulation was hypothesized to control UVS cone distribution. Thyroid hormone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 46 publications
5
40
1
Order By: Relevance
“…This process also occurs in land-locked salmonid species such as the popular fish model, rainbow trout (Oncorhynchus mykiss), which spend their entire lifespan in freshwater systems. In rainbow trout, loss of UVS cones is preceded by the downregulation of the SWS1 opsin gene (Allison et al, 2003;Veldhoen et al, 2006;Raine and Hawryshyn,al., 2006;Raine and Hawryshyn, 2009;Raine et al, 2010). Additionally, consistent upregulation of TR gene expression prior to T4-induced down-regulation of SWS1 suggests that this receptor isoform plays a key role in this developmental process, similar to that found in mice (Raine and Hawryhshyn, 2009;Ng et al, 2010;Raine et al, 2010).…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…This process also occurs in land-locked salmonid species such as the popular fish model, rainbow trout (Oncorhynchus mykiss), which spend their entire lifespan in freshwater systems. In rainbow trout, loss of UVS cones is preceded by the downregulation of the SWS1 opsin gene (Allison et al, 2003;Veldhoen et al, 2006;Raine and Hawryshyn,al., 2006;Raine and Hawryshyn, 2009;Raine et al, 2010). Additionally, consistent upregulation of TR gene expression prior to T4-induced down-regulation of SWS1 suggests that this receptor isoform plays a key role in this developmental process, similar to that found in mice (Raine and Hawryhshyn, 2009;Ng et al, 2010;Raine et al, 2010).…”
Section: Introductionsupporting
confidence: 67%
“…Total RNA was isolated from each juvenile retina. RNA isolation and quantification procedures followed protocols developed in previous studies (Raine et al, 2004;Veldhoen et al, 2006;Raine and Hawryshyn, 2009;Raine et al, 2010). Briefly, samples were homogenized using a Retsch MM301 mixer mill (Retsch GmBH & Co. Ltd KG, Hann, Germany) and total RNA isolated with an Absolutely RNA Miniprep kit (Stratagene, LaJolla, CA, USA).…”
Section: Rna Isolation and Cdna Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Opsin switches in postmitotic photoreceptors are well known in the developing mammalian retina, with ultraviolet/blue (SWS1) opsin expression preceding green (MWS/LWS) opsin expression (Szél et al, 1994;Cornish et al, 2004) and have been observed, during metamorphosis, in the larval eye of the fruit fly (Sprecher and Desplan, 2008) and in young fish (Gan and Novales Flamarique, 2010; references therein). In the retina of juvenile salmonids (alevin and parr stages), for example, "single cones" undergo a TH-induced switch in opsin expression from ultraviolet (SWS1) to blue (SWS2) opsin (Cheng and Flamarique, 2007;Cheng et al, 2009), with the expression levels of thyroid receptor isoforms TR␣ and TR␤ raising after developmental or experimentally induced surges in thyroid hormone (Raine and Hawryshyn, 2009;Gan and Novales Flamarique, 2010;Raine et al, 2010). In adult mammals, comparable opsin shifts have not been described, except minor circadian oscillations of opsin transcript levels (von Schantz et al, 1999), which are thought not to alter the spectral phenotype of the photoreceptor.…”
Section: Discussionmentioning
confidence: 99%
“…In the retina of rainbow trout parr, quantitative RT-PCR analyses have shown that TRa and TRb transcription is up-regulated following 3 days of exogenous thyroid hormone exposure (Raine and Hawryshyn, 2009). This up-regulation is most pronounced in the dorso-temporal retina, the only area with a remaining population of UV opsin-expressing cones at this stage in the animal's life cycle (Cheng and Novales Flamarique, 2007;Cheng et al, , 2009.…”
Section: Tra May Regulate the Uv-toblue Opsin Switch In Differentiatementioning
confidence: 99%